Cotas raciais na UFPA: as percepções de estudantes cotistas sobre suas trajetórias acadêmicas - LEMOS, Isabele Batista de (Universidade Federal do Pará, 2017)
In the field of studies about the functioning of race-based affirmative programs, the research delimits the Amazon region, precisely the Federal University of Pará (UFPA), to analyze the narratives of students who entered into the university by the racial quota system and have graduated or are close to complete their graduation. Through methodology based on life stories, thirteen academics from Law, Social Sciences, Computer Engineering and Medicine were interviewed, in order to make them talk about their experiences during the graduation as black students and as racial quota beneficiaries. The conclusions of this study suggest that, referring to the thirteen students interviewed, the program of UFPA has been effective in providing for these young people the access and the successful stay at the university, although they still face financial difficulties, problems to access cultural benefits and prejudice, both because they are racial quota beneficiaries, both because they are black.